Communities and land in the Huanta (Ayacucho) highlands: the cases of Rodeo Pampa and Iquicha - Pereyra Chávez, Nelson E. (2025)
This article analyzes hoy two peasant communities of Huanta, in Ayacucho, have participated in a process of land usufruct throughout the 20th century. Based on the study of the Rodeo Pampa and Iquicha files, it argues that the possession of communal land is the result of a historical development that began with the configuration of individual and familiar plots, continued with the formation of farms and culminated with the Agrarian Reform and the recognition of the communities. In this process, the peasants claimed ownership of the land through the presentation of documents that they themselves have turned into a moral argument for the defense of their possessions.